Carbon Storage and Carbon Dioxide Emission as Influenced by Long-term Conservation Tillage and Nitrogen Fertilization in Corn-Soybean Rotation - Muhajir Utomo; Henrie Buchari; Irwan Sukri Banuwa; Lanang Koko Fernando; Rahmat Saleh (UNIVERSITY OF LAMPUNG, 2012)
Although agriculture is a victim of environmental risk due to global warming, but ironically it also contributes to global greenhouse gas (GHG) emission. The objective of this experiment was to determine the influence of long-term conservation tillage and N fertilization on soil carbon storage and CO2 emission in corn-soybean rotation system. A factorial experiment was arranged in a randomized completely block design with four replications. The first factor was tillage systems namely intensive tillage (IT), minimum tillage (MT) and no-tillage (NT). While the second factor was N fertilization with rate of 0, 100 and 200 kg N ha-1 applied for corn, and 0, 25, and 50 kg N ha-1 for soybean production. Samples of soil organic carbon (SOC) after 23 year of cropping were taken at depths of 0-5 cm, 5-10 cm and 10-20 cm, while CO2 emission measurements were taken in corn season (2009) and soybean season (2010). Analysis of variance and means test (HSD 0.05) were analyzed using the Statistical Analysis System package. At 0-5 cm depth, SOC under NT combined with 200 kg N ha-1 fertilization was 46.1% higher than that of NT with no N fertilization, while at depth of 5-10 cm SOC under MT was 26.2% higher than NT and 13.9% higher than IT. Throughout the corn and soybean seasons, CO2-C emissions from IT were higher than those of MT and NT, while CO2-C emissions from 200 kg N ha-1 rate were higher than those of 0 kg N ha-1 and 100 kg N ha-1 rates. With any N rate treatments, MT and NT could reduce CO2-C emission to 65.2 %-67.6% and to 75.4%-87.6% as much of IT, respectively. While in soybean season, MT and NT could reduce CO2-C emission to 17.6%-46.7% and 42.0%-74.3% as much of IT, respectively. Prior to generative soybean growth, N fertilization with rate of 50 kg N ha-1 could reduce CO2-C emission to 32.2%-37.2% as much of 0 and 25 kg N ha-1 rates.